HARMONICS LEVEL IMPROVEMENT OF DISTRIBUTED GENERATION INTEGRATED DISTRIBUTION SYSTEM USING UNIFIED POWER QUALITY CONDITIONER - PEREKEBINA EBIAREDE; ATRICK OSHEVIRE (Journal of Engineering Studies and Research, 2022)
In this paper the use of active power filter to improve voltage and current distortion caused by the presence of dispersed generation in the distribution system is investigated. The harmonics produced by photovoltaic distributed generation sources is studied and the unified power quality conditioner is introduced as a technique of minimizing these harmonics generated by the presence of distributed generation. The network is modeled and simulated in ETAP 16.0 software environment and harmonic load flow results show an increase in harmonic level when DG is introduced into the network which is subsequently reduced by the introduction of UPQC into the network.